Improved control of multi terminal direct current voltage source converters using proportional integral and lead lag controllers - Youngmin Gong; Insu Kim; Wonyoung Choi (Scientific Reports)
Abstract In this study, control methods for the converter inner current loop of HVDC systems were evaluated by comparing different combinations of PI controllers and lead-lag compensators. The evaluation was performed on a 3-terminal voltage source converter (VSC)-based multi-terminal direct current (MTDC) system using PSCAD/EMTDC transient analysis simulation. The performance was analyzed under three fault conditions. (alternating current) AC-side single line-to-ground fault, (direct current) DC transmission line fault, and converter disconnection). The results showed that connecting a PI controller to the DC link voltage stabilizer and lead-lag compensators to the power source and load achieved optimal performance with an average overshoot of 78% and an average stabilization time of 398 msec. This represents a 26% reduction in settling time and a 42% increase in overshoot compared to the generic PI controller. The performance was compared by scoring and found to be a 40% increase in control performance. This study demonstrates that lead-lag compensators can significantly improve the control performance of VSC-based MTDC systems.